Mechanosensitive channels Msy1 and Msy2 are required for maintaining organelle integrity upon hypoosmotic shock in Schizosaccharomyces pombe. Issue 6 (22nd July 2014) - Nakayama, Yoshitaka; Hirata, Aiko; Iida, Hidetoshi
Abstract The mechanosensitive channels, Mys1 and Msy2, in fission yeast are localized in the endoplasmic reticulum membrane and control cytoplasmic Ca2+ levels in the hypoosmotic response. We here investigated changes in organellar structures with hypoosmotic shock using transmission electron microscopy. While msy1− and msy2− single mutant cells developed a number of swollen vacuoles following hypoosmotic shock, similar to wild‐type cells, msy1−msy2− double mutant cells only had two abnormally large vacuoles and cracks between the inner and outer nuclear membranes. These results suggest that Msy1 and Msy2 may be involved in maintaining vacuole integrity and protecting the nuclear envelope upon hypoosmotic shock and also that these two channels are functionally complementary.